TWO-WAY FLUID-STRUCTURE INTERACTION SIMULATION ANALYSIS OF SUCTION DEVICE OF LINEAR COMPRESSOR BASED ON UDF TECHNOLOGY - LIANG XiaoYu; MAO Jun; WANG Xin (Jixie qiangdu)
In the paper, the suction device of linear compressor is taken as the research object, and aiming at the transverse bending problem of suction valve plate of linear compressor, the structural control equation of suction valve plate is constructed according to elastic mechanics and plate and shell mechanics. Based on the basic theory of fluid-solid coupling, the fluid control equation, structural control equation and fluid-solid coupling equation are established. Based on 3 D dynamic mesh and UDF（User Defined Function） technology, the bidirectional fluid-solid coupling simulation model of suction device of linear compressor is established, and the performance test experiment of linear compressor is carried out. The flow field characteristics and mechanical behavior of suction device under unidirectional and bidirectional fluid-solid coupling are studied by taking the optimal inlet temperature and inlet pressure obtained from the experiment result as the simulation boundary conditions. The simulation results show that unidirectional and bidirectional fluid-solid coupling are essentially different. In the simulation of unidirectional fluid-solid coupling flow field, the valve plate will not open, but in the bidirectional, a pressure gradient exists between the valve channel and the piston cavity in the bidirectional fluid-solid coupling, while the unidirectional it doesn’t, and the bidirectional fluid-solid coupling simulation is closer to the actual situation, The results can provide theoretical guidance for the structural design and topology optimization of valve plate and suction device.